2021
DOI: 10.3389/fgene.2021.689916
|View full text |Cite
|
Sign up to set email alerts
|

SNAI2-Induced CircMTO1 Promotes Cell Proliferation and Inhibits Apoptosis Through the miR-320b/MCL1 Axis in Human Granulosa-Like Tumor Cells

Abstract: Polycystic ovary syndrome (PCOS), one of the most common types of endocrine diseases, is characterized by a high prevalence among women of reproductive-age. However, its pathogenesis and molecular mechanisms remain unclear. CircMTO1 has been reported to participate in numerous biological processes, but, its role in PCOS progression remains unknown. In the current study, we elucidated the expression and circRNA characterization of circMTO1 in human granulosa-like tumor cells. We found that circMTO1 knockdown pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Further investigations confirmed that circPSMC3 exerted its function by sponging miR-296-3p to regulate PTEN expression. CircMTO1 significantly influenced proliferation and apoptosis rate of GCs through miR-320b, which directly targeted MCL1 in PCOS [55]. Similarly, the expression of circ_RANBP9 was closely associated with GC proliferation and apoptosis; subsequent studies revealed that circ_RANBP9 functioned via the miR-136-5p/XIAP axis in PCOS [56].…”
Section: Circular Rnas and Ovarian Dysfunction In Pcosmentioning
confidence: 94%
“…Further investigations confirmed that circPSMC3 exerted its function by sponging miR-296-3p to regulate PTEN expression. CircMTO1 significantly influenced proliferation and apoptosis rate of GCs through miR-320b, which directly targeted MCL1 in PCOS [55]. Similarly, the expression of circ_RANBP9 was closely associated with GC proliferation and apoptosis; subsequent studies revealed that circ_RANBP9 functioned via the miR-136-5p/XIAP axis in PCOS [56].…”
Section: Circular Rnas and Ovarian Dysfunction In Pcosmentioning
confidence: 94%
“…CircMTO1 was found to mediate the progression of human granulosa-like tumor cells through the miR-320b/MCL1 axis, promoted by increased transcription of SNAI2. Thus, Duan et al concluded that a SNAI2/circMTO1/miR-320b/MCL1 axis is a promoter of human granulosa-like tumor cells in PCOS [108].…”
Section: Role In Pcos Referencesmentioning
confidence: 99%